Penguatan Kapasitas UMKM dalam Menghadapi Aspek Hukum dan Perizinan Pendampingan Hukum bagi Pelaku Usaha di Desa Doyo Baru - Muhammad Khaidir Kahfi Natsir; Dwight Nusawakan; Annisa Fitriah Mudassir; Abdul Malik Mufty (Lembaga Pengembangan Kinerja Dosen, 2025)
Strengthening the capacity of Micro, Small, and Medium Enterprises (MSMEs) is a crucial step in enhancing competitiveness and sustainability in Indonesia, especially in rural areas such as Doyo Baru Village. Many MSME actors in this village face difficulties in understanding and fulfilling the legal aspects and permits required to operate their businesses legally and effectively. This research aims to provide comprehensive legal assistance to MSME actors, focusing on understanding regulations, licensing processes, and consumer rights. The methodology used in this research is a participatory approach that includes training, group discussions, and individual consultations. The results of this activity show a significant increase in the understanding of legal and licensing aspects among MSME actors, with 80% of participants reporting improved knowledge and confidence in facing legal challenges. Additionally, participants have started to apply the knowledge gained in their daily practices, such as business registration and consumer protection. The conclusion of this research emphasizes the importance of ongoing support for MSMEs to adapt to regulatory changes and improve their competitiveness in the market. It is hoped that this legal assistance program can serve as a model for other regions in efforts to empower MSMEs.